2013
DOI: 10.1002/gj.2481
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of the Yangchang Mo-bearing granite in the Xilamulun metallogenic belt, NE China: geochemistry, zircon U-Pb ages and Sr-Nd-Pb isotopes

Abstract: The Yangchang granite‐hosted Mo deposit is typical of the Xilamulun metallogenic belt, which is one of the important Mo–Pb–Zn–Ag producers in China. A combination of major and trace element, Sr, Nd and Pb isotope, and zircon U–Pb age data are reported for the Yangchang batholith to constrain its petrogenesis and Mo mineralization. Zircon LA‐ICPMS U–Pb dating yields mean ages of 138 ± 2 and 132 ± 2 Ma for monzogranite and granite porphyry, respectively. The monzogranites and granite porphyries are calc‐alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…1c). Although these deposits have been extensively reported (e.g., Zhang et al, 2010a;Wu et al, 2011a;Ma et al, 2013;Zeng et al, 2013Zeng et al, , 2014Shu et al, 2014), the genesis of the magmatism and the controlling factors of Mo enrichment remain obscure. In this contribution, three deposits (Yangchang, Haisugou and Shabutai) in this area have been investigated.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…1c). Although these deposits have been extensively reported (e.g., Zhang et al, 2010a;Wu et al, 2011a;Ma et al, 2013;Zeng et al, 2013Zeng et al, , 2014Shu et al, 2014), the genesis of the magmatism and the controlling factors of Mo enrichment remain obscure. In this contribution, three deposits (Yangchang, Haisugou and Shabutai) in this area have been investigated.…”
Section: Introductionmentioning
confidence: 96%
“…1). Many studies have been carried out during the past decade in order to identify the geological characteristics, isotopic ages, ore genesis, origin and evolution of the associated intrusions as well as the corresponding geodynamic settings (Chen et al, 2008;Qin et al, 2008Qin et al, , 2009Shu et al, 2009Shu et al, , 2014Wan et al, 2009;Yan, 2009Yan, , 2012Zeng et al, 2010Zeng et al, , 2012Zeng et al, , 2013Zeng et al, , 2014Zhang et al, 2009aZhang et al, , 2010aZhang et al, , b, 2012Liu et al, 2010;Zhou et al, 2010Zhou et al, , 2012Wu et al, 2011aWu et al, , 2014Ma et al, 2013;Meng et al, 2013;Sun et al, 2013). The findings of some of these studies have shown that the Mo mineralization in the southern part of Xilamulun can be clustered into three groups, i.e., 250-210, 180-150 and 140-110 Ma (Zhang et al, 2009a).…”
Section: Introductionmentioning
confidence: 98%
“…8b). Meanwhile, the closure of the Paleotethys and collision between the Qiangtang Block and Asia also occurred during the Triassic (Kapp et al, 2000;Zhang et al, 2006;Roger et al, 2008). However, as this block is relatively small compared with the NCB and SCB and is far away from our study area, the impact of this orogenic event on the strike-slip faulting is uncertain.…”
Section: Geodynamic Implications On the Triassic Tectonics Of Centralmentioning
confidence: 88%
“…1b), is considered as the suture zone between the North China Block and the Siberia Block (Tang, 1990;Li, 2006). It is also the controlling fault for the Mesozoic MoCu metallogenic belt (L. Wu et al, 2011;Zeng et al, 2013). The Xilamulun Fault extends about 700 km from Hexigten east to Changchun, which is documented by both geological (Li, 2006) and geophysical evidence, such as aeromagnetic and gravity anomalies and a magnetotelluric profile Chen et al, 2008).…”
Section: Xilamulun Faultmentioning
confidence: 98%
See 1 more Smart Citation